Performance and Applicability Analysis of Indirect Evaporative Cooling Units in Data Centers Across Various Humidity Regions - Qian Wei; Jun Lu; Xiaoping Xia; Bin Zhang; Xiang Ying; Leihong Li (Buildings)
Indirect evaporative cooling (IEC), which utilizes natural cooling sources, is an advanced and promising technology to reduce the energy consumption of cooling systems in a data center (DC). This study presents a model of an IEC air-conditioning unit in a DC using TRNSYS simulation software validated using actual operational data to investigate the adaptability of IEC units in data centers located in regions with varying humidity levels, providing a reference for their application and promotion in DCs. Based on this premise, the authors analyzed the meteorological characteristics of Urumqi (a dry region), Beijing (a region with medium humidity), and Shanghai (a region with high humidity), which are representative cities in different humidity zones. The analysis identified the annual operating hours of the unit’s three operation modes, including fresh-air indirect heat transfer (FAIHT), IEC, and hybrid. Simultaneously, the authors conducted a simulation of the unit’s yearly energy consumption and determined time change curves for annual energy consumption, hourly coefficient of performance (COP) throughout the year, and mechanical cooling in various locations. The results indicate that IEC air-conditioning systems are highly effective in promoting the efficiency of data centers in various humidity regions. Dry locations demonstrate the greatest adaptability, followed by regions with medium humidity and, finally, regions with high humidity. The findings indicate that IEC units provide significant energy efficiency and cost-effectiveness when deployed in typical urban DCs across various humidity zones in China. The average annual power-usage effectiveness (PUE) of each city’s DC utilizing the unit is less than 1.3, and the unit’s annual operational cost savings exceed 30%.